Genotype x environment interaction for weight at 365 days in Mediterranean buffaloes - Rodrigues, Fernando Barreto; Souza Carneiro, Paulo Luiz; Ramos, Alcides de Amorim [UNESP]; Ambrosini, Diego Pagung; Mendes Malhado, Carlos Henrique (Empresa Brasil Pesq Agropec, 2015)
The objective of this work was to verify the presence of the genotypes x environments interaction (GxE) for weight at 365 days of age in the Mediterranean breed of buffaloes, using models of reaction norms through random regression. The standard animal model and the models of reaction norms were tested, and the hierarchical model reaction norm (MRN) was evaluated with one and two steps. The homoscedastic hierarchical model of reaction norms with one-step (HMRNHO1s) had the best fit, based on three criteria for comparison. The direct heritability estimates for this model ranged from 0.19 to 0.78, with environment improvement. Besides, direct breeding values (scale effect) changed for some breeders, which indicates the existence of GxE interaction. The Spearman correlations were high, both in the comparison between the standard animal model and MRN, as in the comparison between low, medium, and high management levels in HMRNHO1s. Therefore, although there is GxE interaction, the ranking of breeding animals is not significantly affected by the models. The majority of buffaloes is formed by animals with robust genotypes, which are less sensitive to environmental changes.
Keywords: scale effect; environmental gradient; hierarchical model; reaction norms; random regression; breeding value